Increased cancer incidence in "cold" countries: An (un)sympathetic connection?. (April 2020) - Mravec, Boris; Tibensky, Miroslav
Abstract: Published data has shown that there is an unexpected, significantly increased cancer mortality and incidence in countries with low or subnormal environmental temperatures. There have been several hypotheses developed to elucidate the mechanisms behind these findings. It is well documented that cold represents a very efficient stressor that activates sympathetic nerves and increases tissue and plasma norepinephrine levels. Importantly, recently accumulated data indicate that norepinephrine can stimulate carcinogenesis and the progression of cancer. Therefore, we suggest that the effect of a cold environment on cancer incidence and mortality might be mediated, at least partially, by norepinephrine released from sympathetic nerves in response to cold. Data supporting this hypothesis are discussed here and potential preventive approaches are described. Highlights: Significantly increased cancer incidence was found in countries with low or subnormal environmental temperatures. Cold exposure significantly activates sympathetic nervous system. Sympathetic nervous system participates in induction and progression of cancer. Cold-related increase of cancer incidence might be, at least partially, mediated by sympathetic nervous system.